The Post-Harmonisation Health and Safety Challenges of Construction Industry Managers - Richard Phelps; Janis Jansz; Ping Chang; Apurna Ghosh (Safety)
To minimise the occurrence of injuries, illnesses and deaths due to work-related causes, it is important to have effective workplace health safety legislation that is known and used. The introduction of more stringent workplace health and safety legislation across Australia has brought greater responsibility, and harsher penalties, for managers. The importance of the role those in management play in influencing and shaping a culture of safety is well researched, but little has been done to determine whether those in management are ready to assume that role. This study aimed to identify what has informed Western Australian construction industry managers who are working within the mining sector and ultimately shaped their approach to occupational health and safety. NVivo software was used to analyse the data by the creation of codes and subcodes to identify themes and subthemes. Analysis of two focus groups’ participants’ responses identified that many managers had insufficient work health and safety education to understand their obligations and that other challenges include insufficient preparedness of managers, particularly newly promoted supervisors and other management staff, rapid promotion, and the bureaucracy of modern workplace health and safety. The findings from this study can assist organisations to better prepare managers to fulfil their workplace health and safety obligations and reduce some of the post-harmonisation challenges.